Improved diagnosis of extrapulmonary tuberculosis in adults with and without HIV in Mbeya, Tanzania using the MPT64 antigen detection test - Erlend Grønningen; Marywinnie Nanyaro; Lisbet Sviland; Esther Ngadaya; William Muller; Lisete Torres; Sayoki Mfinanga; Tehmina Mustafa (Public Library of Science (PLoS), 2022)
Extrapulmonary tuberculosis (EPTB) in People Living with HIV (PLWHIV) is a diagnostic challenge. Our immunochemistry based MPT64 antigen detection test has shown improved sensitivity compared to current laboratory tests in the resource limited diagnostic setting. The aim of this study was to validate the implementability and diagnostic performance of the test in PLWHIV and HIV negative adults in a HIV endemic Tanzanian setting. Adult (>18 y) presumptive EPTB patients were prospectively enrolled at Mbeya Zonal Referral Hospital and followed to the end of treatment or until an alternative diagnosis was reached. Suspected sites of infection were sampled and were subject to routine diagnostics, GeneXpert MTB/RIF assay and the MPT64 test. The performance of the diagnostics tests was assessed using a composite reference standard that included clinical suspicion, mycobacterial culture, response to anti-tuberculosis (TB) therapy, cytological and radiological findings. Patients (N = 168) were categorized as 21 confirmed TB, 23 probable TB and 44 possible TB cases, 69 patients were categorized as non-TB cases and 11 were uncategorized. In the TB group, the three most common infections were adenitis (41%), peritonitis (19%) and pleuritis (14%). The TB and non-TB groups did not differ in HIV seropositivity (46% vs 42%) Among HIV negative and PLWHIV, the MPT64 test had a sensitivity of (91% vs 78%), specificity (75% vs 86%), positive predictive value (80% vs 88%), negative predictive value (89% vs 74%), and accuracy (84% vs 81%), respectively. Performance was not significantly reduced in PLWHIV, and sensitivity was higher than in the currently used tests, including the GeneXpert MTB/RIF assay. The MPT64 test improved the diagnosis of EPTB, irrespective of HIV status. The test performed better than currently used diagnostic test. The test was implementable in a tertiary level hospital with basic pathology services in a HIV endemic Tanzanian setting.